2020
DOI: 10.1111/cid.12883
|View full text |Cite
|
Sign up to set email alerts
|

Immediate implant placement and provisionalization: Aesthetic outcome 1 year after implant placement. A prospective clinical multicenter study

Abstract: Background Prospective aesthetic outcomes on a high number of patients after immediate implant placement and provisionalization (IIPP) are lacking. Purpose To analyze the aesthetic outcome after IIPP. Materials and Methods One hundred consecutive patients with a failing maxillary incisor were provided with an immediately placed and provisionalized nonloaded implant using a flapless procedure and palatal implant positioning. The remaining gap buccally was filled with a bone substitute. Preoperatively (T0), 2 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…In addition, they stated that early placed implants tended to be superior to delayed-placed implants with respect to STL level. So cautiously, it can be stated that performing FIIPP conform this standardized protocol [ 13 , 15 ] and shows better results at the point of soft tissue level than early or delayed protocols. Further research is necessary to confirm or decline these assumptions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, they stated that early placed implants tended to be superior to delayed-placed implants with respect to STL level. So cautiously, it can be stated that performing FIIPP conform this standardized protocol [ 13 , 15 ] and shows better results at the point of soft tissue level than early or delayed protocols. Further research is necessary to confirm or decline these assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria were (1) smoking habits exceeding more than 10 units a day, (2) pregnancy, (3) bone diseases or a history of irradiation, (4) ASA III or higher. Both surgical and restorative procedures were performed following a standardized protocol [ 13 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not yet set whether the use of alternative techniques such as a flapless approach, palatinal/lingual implant position, filling the bone gap between the implant and buccal alveolar wall, abutment configuration and crown design might be better approaches to limit the degree of recession of the mucosa (Grunder, 2011; Kan et al., 2018; Lee et al., 2016; Lin et al., 2014; Raes et al., 2011). A prospective multicentre case series in which a flapless immediate implant placement approach was applied to 100 patients without additional SCTG reported very favourable aesthetic outcomes after 1 year (Groenendijk et al., 2020). Latter authors showed an improvement in mucosal level and a stable contour of the alveolar process the first year after treatment.…”
Section: Discussionmentioning
confidence: 99%